The Arctic convoy [videorecording (DVD)] - Siebenherz, Christian; Gudmestad, Lars; Eeg, Harald Rosenløw, 1970-; Santelmann, Tobias, 1980-; Christiansen, Anders Baasmo, 1976-; Ellingsen, Heidi Ruud; Hodneland, Preben; Lundgren, Adam; Ranes, Jon; Waastad, Olav; Repshus, Kristian; Ditlev-Simonsen, Fredrik Stenberg; et al. (Magnolia Home Entertainment, 2024)
In 1941, the leader of a convoy carrying vital military supplies to Allied forces decides to proceed through treacherous, enemy infested waters despite the recall of their military escort. Fighting for their lives against merciless German air and naval attacks, the 35 civilian merchant ships brave brutal Arctic seas to bring critical support to soldiers on the front lines.